EFL TEACHERS' PERCEPTION AND PRACTICE ON FORMATIVE ASSESSMENT - Rusli, - (2017)
National Curriculum involves EFL school teachers to integrate formative assessment in their classroom implementations. Most teachers used summative assessment as a standard of measuring students' achievement. This study aims at obtaining better insights into EFL teachers' conceptual understanding of formative assessment in EFL teaching. The research questions are (1) What are teachers' perception on the concept of formative assessment in EFL classrooms? and (2) How do teachers practice formative assessment in their classrooms? This research employs a case study method. For these purposes, three senior high school EFL teachers from Kabupaten Kepulauan Meranti - Riau are involved as respondents to find out the EFL teachers' perception and practice of formative assessment, and researcher uses a questionnaire, interview and observation to collect the data. Results of data analysis show that teachers have good perception and practice which are implemented in their classroom. The researcher also notices that the similarities between perception and practice do not guarantee that every teacher will consistently implement formative assessment plans that they have designed earlier. Hence, they sometimes just do formative assessment in the same way for every subject given to students. Keywords: teachers' perception, teachers' practice, formative assessment